UPAYA PENGENALAN KULINER LOKAL INDONESIA DALAM MATERI AJAR BIPA MELALUI MEDIA AUDIOVISUAL - Fera Umi Farinda; Khaerunnisa (Universitas Negeri Surabaya, 2023)
Introducing local Indonesian culture as an effort to assit the goverment in inscreasing the interest of cultural tourists who have good and interesting regional potential. This study aims to describe local Indonesian cuisine as material for BIPA students through audiovisuals. This research method used is descriptive-qualitative. Through this learning, it is expected to abe to preserve and also maintain national identity through this BIPA learning. One of the styles that can be used as BIPA’s teaching materials is local Indonesian culinary. This research also involves audiovisual media as an intermediary in the learning process. Audiovisual media was chosen because it is a supporting factor for succesfull learning and is also the right language to introduce cultures in Indonesian. Through this audiovisual media, it can also foster creativity and critica thinking for BIPA students. Key Words: culture, audiovisual, BIPA (Bahasa Indonesian for Nonative Speaker)